Innovative Strategies and Technologies in Waste Management in the Modern Era Integration of Sustainable Principles, Resource Efficiency, and Environmental Impact - Mashudi; Rahayu Sulistiowati; Suryo Handoyo; Erni Mulyandari; Nur Hamzah (International Journal of Science and Society, 2023)
In the context of waste management in the modern era, environmental challenges are increasingly complex. Innovative strategies and sustainable technology are important to answer this problem. This study aims to analyze the environmental impact of implementing innovative strategies and technologies in waste management and to provide recommendations for mitigating negative impacts. The literature study method is used to collect and analyze relevant data. The results of this research illustrate the positive potential of innovative strategies in waste management but also emphasize the need for careful mitigation measures to reduce negative impacts on the environment. In facing the challenges of waste management, innovative strategies, and technologies provide real opportunities to achieve environmental sustainability in the future.